Analysis of impacts caused by direct course interventions that Czech National Bank started in 2013 regarding development of Balance of Payments in 2010 - 2015 - Peterka, Pavel (2016)
On november 7th the Czech National Bank began with direct course interventions consistent with its legal mandate to achieve domestic currency depreciation after using up the tool of interest rates. The motivation of the Czech National Bank behind this action was to come closer to the inflation target and to avert the threat of a deflation. The main content of thesis is the analysis of macroeconomic indexes in the time period of 2010-2015 primarily GDP, net export and the balance of payments. The time period offered a look into a short period of time before and after the Czech National Bank began with the direct course interventions. Another very important content of this thesis is a brief summary of some of the arguments against or in favor of such action. The main targets of the thesis are evaluation of impacts that were caused by this action and evaluation of its legitimacy. Among the used methods of research are mostly analysis, comparison, analogy and syntesis. The conclusion based on the results of the analysis and arguments of both sides is that the interventions were not justified enough and that they were not the main cause of the economic recovery that took place in the Czech Republic in 2013. The analysis indicates that recovery had started a few months before the interventions even began and that the recovery was based mainly on the recovery of domestic and foreign demand and on the growth of the car industry.